Study of Teaching Approaches to Create Creative Works and Multimedia from Character Design Skills - Chaiyajak, Nichakan (DEC Journal : Art and Design, 2025)
Currently, education must be designed to suit learners and promote students’ creativity, leading to the creation of new innovations. Therefore, teaching should be tailored to meet learners’ needs, developing them with essential future skills. This research is an experimental study aimed at exploring teaching theories and designing learning activities that foster creative character design, and summarizing the body of knowledge. The research found that a combination of three instructional approaches is recommended: 1) Project-Based Learning, 2) Creative-Based Learning, and 3) Brain-Based Learning. Subsequently, learning activities were developed, divided into three main components: Activity 1 involved selecting topics to create projects, practicing analysis, exploration, and addressing personal and social needs, utilizing principles of effective collaboration, problem-solving, and inquiry. Activity 2 focused on developing ideas, evaluating approaches to extend characters into creative works and multimedia, and enhancing thinking skills. Activity 3 aimed to refine projects through personalized learning. Among the 38 participants, 19 (50%) chose topics related to character design, with the greatest interest in creating concept art, followed by animation, game design, corporate identity, art toys, and keycaps. Crucially, instructors must serve as mentors, providing individualized attention and fostering personal development based on each student’s potential.